Twelve week calcium collagen chelate or calcium plus vitamin d supplementation does not affect bone metabolism in trained cyclists - Greer, B.; Mojock, C.; Arjmandi, B.; Kim, J. S.; Ormsbee, M.; Panton, L. (Journal of Science and Cycling, 2022)
The purpose of the present study was to determine whether 12 weeks of calcium collagen chelate (CCC) supplementation during habitual training would affect body composition, bone mineral density (BMD), and biomarkers of bone metabolism in competitive cyclists. Twenty trained (maximal aerobic capacity > 50 ml/kg/min, mean training volume: 28 h/wk) male cyclists performed maximal exercise testing and 40-km time trials (TT) on an electronically braked cycle ergometer. BMD of the whole body, lumbar spine (L1-L4), and both hips were measured via dual-energy X-ray absorptiometry (DXA). The cyclists were assigned to one of two groups: 1) 6 g/d of CCC with 600 mg calcium and 400 IU vitamin D or 2) a placebo control (CON) composed of an inert compound with equivalent calcium and vitamin D concentrations to CCC. Two-way repeated measures ANOVA and Pearson product-moment correlations were used to determine the effects of CCC or CON supplementation on BMD, bone alkaline phosphatase (BAP), tartrate resistant acid phosphatase 5b (TRAP5b), and sclerostin (SCL); significance was accepted at p < 0.05. No within- or between-group differences in dependent variables were found. Significant correlations were found between weekly training volume and TRAP5b (r = 0.531), BAP and VO2 max (r = -0.561), and BAP/TRAP5b ratio and both right/left hip BMD (r = -0.649 and r = -0.646, respectively). In conclusion, 12 weeks supplementation of CCC does not affect body composition, BMD, or biomarkers of bone metabolism in trained, competitive cyclists in comparison to equivalent amounts of calcium plus vitamin D.